Immune Response to anti-HBs Antibodies in Health Workers Following Hepatitis B Vaccination - Dinna Rakhmina; Wahdah Norsiah; Tini Elyn Herlina; Norhafizah Mulia Sari; Reza Pertiwi; Rizka Ariani; Sahri Rahman (Medical Laboratory Technology Journal, 2021)
According to Regulation No. 53 of 2015 of the Minister of Health of the Republic of Indonesia, a high risk of HBV infection in health workers is a problem that requires attention, and vaccination knowledge is critical to reducing these risk factors. Furthermore, because some people do not produce a sufficient antibody-forming (anti-HBs) response to HBsAg, testing for evidence of protective immunity against hepatitis B vaccination is required (Hepatitis B Surface Antigen). The purpose of the study was to determine the mapping of the characteristics of anti-HBs antibodies response after hepatitis B vaccination in health workers in terms of age, gender, ethnicity, smoking habits, obesity, vaccination frequency, last time of vaccination. Sixty vaccinated health workers were used to creating the research sample. Anti-HBs levels/titers in serum were measured using the Enzyme-Linked Immunosorbent Assay (ELISA) method, and a questionnaire was used to compile the data for this study. Age, gender, smoking, obesity, and vaccination dose were all used to map the outcomes of the anti-HBs antibody immune response study. Anti-HBs antibody response in health workers was graded as poor in 36 people (60%) and strong in 24 (40%). Regarding ethnic origin, lifestyle, obesity, and vaccination dose (frequency), there was no significant link between post-vaccination anti-HBs antibody response in health workers. In terms of age and gender, there is a strong association between post-vaccination anti-HBs antibody responses in health workers. Low antibody titers should be revaccinated to enhance anti-HBs titers, and health workers who smoke should quit because it reduces the levels of anti-HBs titers produced clinically.